Burr to Bone Time for Joint Preparation in Minimally Invasive Foot and Ankle Fusion Surgeries: A Cadaver Study - Maksat Idris MS, BS; Ettore Vulcano MD; Bonnie Y. Chien MD (Foot & Ankle Orthopaedics)
Category: Ankle; Midfoot/Forefoot Introduction/Purpose: Minimally invasive surgical (MIS) techniques have been implemented in various foot and ankle procedures, including joint arthrodesis. While these techniques can be effective in reducing complications and improving outcomes, there remains variability with surgeon learning curves, the type of instruments used, and approach to intraoperative imaging. This study seeks to aid surgeons through more reproducible guidelines by measuring the time needed for joint preparation with an MIS specific burr. Methods: A total of 8 cadaveric limbs (4 left and 4 right feet) were used for the preparation of the 1st metatarsophalangeal (MTP), 1st tarsometatarsal (TMT), talonavicular (TN), subtalar and ankle joints. The active burr use time to debride all cartilage from each joint was recorded. Each joint was prepared with an open approach to precisely determine the amount of time needed for cartilage removal. Descriptive statistics and a Kruskal-Wallis with post-hoc comparisons were used to analyze the data. Results: The 1st MTP was prepared with a mean (SD) time of 54.49 (34.65) seconds; the 1st TMT 51.82 (19.69) seconds; the TN joint 87.89 (43.77) seconds; the subtalar joint 59.46 (37.84) seconds; and the ankle joint 95.59 (54.99) seconds. Only the ankle joint preparation times compared with 1st MTP, 1st TMT and subtalar joints were significantly longer. Conclusion: This study provides burr time metrics for joint debridement in MIS foot and ankle arthrodesis procedures. Although there remains variability in types of burrs used, joint sizes and individual experience with the instruments, the timing of joint preparation can be an objective reference for surgeons to effectively and safely perform minimally invasive techniques. Figure 1. Comparison of joint preparation time across different joints The error bars depict one standard deviation of uncertainty. Asterisk (*) lines indicate a statistically significant difference (P < 0.05) based on unadjusted P values from the Dunn post hoc group comparisons. *Abbreviations: metatarsophalangeal (MTP), tarsometatarsal (TMT), talonavicular (TN).